Exploration of mood spectrum symptoms during a major depressive episode: The impact of contrapolarity—Results from a transdiagnostic cluster analysis on an Italian sample of unipolar and bipolar patients - Ludovico Mineo; Alessandro Rodolico; Giorgio Alfredo Spedicato; Andrea Aguglia; Simone Bolognesi; Carmen Concerto; Alessandro Cuomo; Arianna Goracci; Giuseppe Maina; Andrea Fagiolini; Mario Amore; Eugenio Aguglia (European Psychiatry, 2022)
Abstract